Enhancing vocational education through the teaching factory model: A study on industry-education collaboration - Wahyudin, Diding; Hanafi, Ivan; Ahmad, Masduki (Edelweiss Applied Science and Technology, 2025)
This study explores enhancing vocational education through the Teaching Factory model, focusing on the collaboration between industry and educational institutions. The research investigates how industry partnerships can improve the quality of vocational training by providing students with hands-on experience in real-world manufacturing environments. The study employs a mixed-methods approach, combining qualitative interviews with educators, industry partners, and students alongside quantitative data from surveys to assess the outcomes of industry-education collaboration. The findings indicate that the Teaching Factory model significantly enhances students’ practical skills, increases their employability, and fosters closer industry-academic ties. However, challenges such as resource limitations, curriculum alignment, and the need for continuous industry involvement were identified. The study concludes that the Teaching Factory effectively bridges the skills gap in vocational education. Still, its success depends on sustained collaboration, adequate infrastructure, and alignment with industry needs. The research offers practical recommendations for educational institutions and policymakers to optimize industry engagement in vocational training programs.